Carbon fiber - Bajpai, P. (Pratima) (Elsevier, 2021)
Carbon Fiber, Second Edition, brings together available information on the production, properties, application and future of carbon fibers. This book will be of interest to those involved in the investigation of carbon fiber, carbon fiber manufacturing, and users. In addition, the recycling of carbon fiber reinforced polymers and the manufacturing of composites from recycled carbon fiber reinforced polymers are discussed. The book offers in-depth coverage on the production of carbon fiber and the global carbon fiber market, demand and major growth drivers. Carbon structures from biowaste, waste lignin and novel processes to obtain high purity lignin are presented, along with future directions.